L’entrée au Parlement des premières députées de la Seconde République espagnole : Clara Campoamor, Victoria Kent, Margarita Nelken, élues de l’assemblée constituante (juillet-décembre 1931) - Catherine Saupin (Genre & Histoire)
On May 8, 1931, Spanish women obtained the right to be elected by decree of the provisional government of the Second Republic. This article examines the entry into politics of the first women elected to the Constituent Assembly of 1931. It aims to understand how these women eased themselves into parliamentary work during the constituent process and how they were admitted. The examination of the portrait of the three pioneers ‒ Clara Campoamor, Victoria Kent and Margarita Nelken‒, the study of C. Campoamor and V. Kent’s involvement in the debate on women’s right to vote and the analysis of the reception given to the three deputies within the parliamentary chamber and in the press testify to an accession to Parliament marked by political confrontation and not without resistance.